2010
DOI: 10.1111/j.1365-2605.2010.01091.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of serum- and glucocorticoid-inducible kinase-1 in regulating torsion-induced apoptosis in rats

Abstract: Serum- and glucocorticoid-inducible kinase-1 (SGK1) is a serine/threonine protein kinase that responds to various stimuli and mediates cell survival. Although it is known that testicular torsion leads to testicular damage and male infertility, the role of SGK1 in torsion remains unclear. This study investigated whether torsion-induced apoptosis is associated with changes in phosphoinositide-dependent protein kinase-1 (PDK1), SGK1 and forkhead transcription factor FOXO3a expression and/or phosphorylation in rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 57 publications
(107 reference statements)
0
3
0
Order By: Relevance
“…Total RNAs were isolated from rat kidney and liver tissues with Trizol reagent (Invitrogen-Life Technologies, Grand Island, NY, USA) as described 37 . Two micrograms of total RNA was reverse transcribed to synthesize cDNA using ThermoScript™ RT-PCR System (Life technologies, Grand Island, NY, USA) for RT-PCR.…”
Section: Methodsmentioning
confidence: 99%
“…Total RNAs were isolated from rat kidney and liver tissues with Trizol reagent (Invitrogen-Life Technologies, Grand Island, NY, USA) as described 37 . Two micrograms of total RNA was reverse transcribed to synthesize cDNA using ThermoScript™ RT-PCR System (Life technologies, Grand Island, NY, USA) for RT-PCR.…”
Section: Methodsmentioning
confidence: 99%
“…Cho et al (2010) reported a decrease in plasma LH concentrations in both the sham and torsion groups in their study, and suggested that the reduction in this hormone could be associated with the effect of stress on the hypothalamus-pituitary–gonadal axis. The same study reported serum testosterone levels to be decreased as a result of the reduction of LH, while an evaluation of FSH levels – an indicator of spermatogenesis – revealed a minimal decrease in the torsion groups [ 31 ]. In the present study, decreases in serum FSH, LH and testosterone levels were detected in the torsion groups when compared with the control group, which supports the previous findings in literature.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown that SGK1 promotes the proliferation and anti-apoptosis of immature SCs [ 58 ] through PI3K, PDK1, AKT signaling pathways [ 59 , 60 ], regulates the protein synthesis and cytoskeleton of mature SCs to change the structure of BTB [ 60 ], and promotes spermatogenesis. In addition, SGK1 highlights the role of FoxO3a in regulating oxidative stress [ 61 ], which can damage BTB by destroying BTB-associated junction proteins and inducing apoptosis of Sertoli cells, leading to testicular damage and spermatogenesis disorders [ 62 ], which could lead to male infertility [ 63 ].…”
Section: Sgk1 Involvement In Gametogenesismentioning
confidence: 99%